Emotional Intelligence on Burnout with Mediation of Self-Efficacy in Yos Sudarso Hospital Padang - rinaldo permana putra; Chichi Andriani (Universitas Negeri Padang, 2021)
The purpose of this study was to analyze: (1) The effect of emotional intelligence on burnout in nurses at Yos Sudarso Padang Hospital. (2)The influence of emotional intelligence on self-efficacy at the nurses at Yos Sudarso Padang Hospital. (3)The influence of self-efficacy on burnout at Yos Sudarso Padang Hospital. (4)The effect of emotional intelligence on burnout in nurses at Yos Sudarso Padang Hospital through self-efficacy. The population at that studying where all nurss at Yos Sudarso Padang Hospitality, totaling 177 people. While the number of samples in this study, namely the entire population was made a sample of 123 nurses using proportional clustered simple random sampling. The analysis technique used is SEM analysis using smart PLS3. The results of this study indicate that: (1) Emotional Intelligence has a significant negative effect on the burnout in nurse at Yos Sudarso Padang Hospital. (2)emotional intelligence as in up to positively influenced in self efficacy in nurse at Yos Sudarso Padang Hospital. (3)Self-efficacy as in up to negatively influenced in they tendency from burnout in nurse at Yos Sudarso Padang Hospital. (4)Emotional-intelligence as in significantly influenced in burnout through self efficacy in nurse at Yos Sudarso Padang Hospital.